Uma análise jurídico-penal do processo de criminalização do terrorismo internacional : obstáculos dogmáticos na tipificação do fenômeno e novas perspectivas de enfrentamento - Machado Júnior, Elisio Augusto de Souza (2018)
The research presents a critical approach about the dogmatic obstacles identified in cases of international terrorism typification. Considering the assumptions of systemic validity of criminal law, the research, through the method of review and comparative analysis of international documents, questions the scientificity in the choice for the autonomous criminalization of conduits to him related. The criminal law has suffered with the inflows of the globalisation process, requiring the overcoming of old dogmas. This new dynamic has guided the abandonment to the rigidity of a criminal science focused on the national scope, putting the problem about terrorism in an international plan. There is, indeed, a clear need for concepts and ways of coping so far used should undergo a thorough review. Terrorism is the most emblematic example of this new order, where the criminal types edited, due to the own terminological vagueness, by reason of their own terminological imprecision, disfigured a series of elementary precepts legitimating, from the principle of legality, the valid imputation of a conduct. The research seeks to assess whether there is legitimacy in the use of criminal law to deal with international terrorism, analyzing if the international criminal law and humanitarian law, isolated or in combination, would not be more appropriate ways to that adopt a minimally harmful output to the rights and fundamental guarantees committed in the process of criminalization.